Neurostimulation to improve level of consciousness in patients with epilepsy - Gummadavelli, Abhijeet (Neurosurg Focus, 2015)
When drug-resistant epilepsy is poorly localized or surgical resection is contraindicated, current neurostimulation strategies such as deep brain stimulation and vagal nerve stimulation can palliate the frequency or severity of seizures. However, despite medical and neuromodulatory therapy, a significant proportion of patients continue to experience disabling seizures that impair awareness, causing disability and risking injury or sudden unexplained death. We propose a novel strategy in which neuromodulation is used not only to reduce seizures but also to ameliorate impaired consciousness when the patient is in the ictal and postictal states. Improving or preventing alterations in level of consciousness may have an effect on morbidity (e.g., accidents, drownings, falls), risk for death, and quality of life. Recent studies may have elucidated underlying networks and mechanisms of impaired consciousness and yield potential novel targets for neuromodulation. The feasibility, benefits, and pitfalls of potential deep brain stimulation targets are illustrated in human and animal studies involving minimally conscious/vegetative states, movement disorders, depth of anesthesia, sleep-wake regulation, and epilepsy. We review evidence that viable therapeutic targets for impaired consciousness associated with seizures may be provided by key nodes of the consciousness system in the brainstem reticular activating system, hypothalamus, basal ganglia, thalamus, and basal forebrain.